Do Posterior Neck Lumps Need Ultrasound Evaluation: A Case Series of 623 Neck Ultrasound Studies at a Single Institution - Atif Siddiqui; Nicholas Chua (SAGE Publishing, 2024)
Introduction/Objectives: Neck lumps are a common presentation to primary care services. The aetiology of posterior neck lumps is poorly explored in the literature, and therefore remain a concern to patients and clinicians. This often results in an urgent referral for ultrasound assessment. The authors of this study sought to evaluate the aetiology of posterior neck lumps from a radiological perspective, to assess whether ultrasound can be used as a useful adjunct, rather than a first-line urgent investigation. Methods: A retrospective case series was carried out, examining all primary care referred ultrasound studies for assessment of posterior neck lumps, performed at a single institution in Essex, United Kingdom, over a period of over 10 years dating between 2nd February 2012 to 8th November 2022. Data was collected on: patient age at the time of study, patient sex, whether the lump was single or multiple as palpated and documented by the primary care physician, size of the lump to the nearest 0.5 cm as documented on ultrasound using the longest dimension, sonographic diagnosis and any follow up imaging (not limited to ultrasound). Results: A total of 623 neck ultrasounds were performed on 615 adults. Of the overall radiological diagnoses made from the 623 scans, 555 (89.09%) scans were benign, 63 (10.11%) scans had no lump found on sonography, and 3 (0.48%) scans showed malignancy. In the remaining 2 (0.32%) scans, the lump was deemed indeterminate. The most common aetiologies for benign lumps were due to: normal lymph nodes (n = 263; 42.21%), lipomas (n = 152; 24.39%), and benign dermal cysts (n = 105; 16.85%). All 3 malignant cases had co-existing anterior and posterior neck lumps. Conclusions: Given that the overwhelming majority of posterior neck lumps in our study had benign findings, we propose that patients with solitary or even multiple posterior neck lumps alone, regardless of size can either be investigated routinely or can be reassured depending on other clinical examination characteristics. Patients who have the presence of co-existing anterior and posterior neck palpable neck lumps justifies urgent or 2-week wait radiological investigation.